Analisis Attitude Terhadap Penunjukan Basuki Tjahaja Purnama Sebagai Komisaris Utama Pertamina dalam Kolom Komentar Instagram Harian Kompas - Ahmad Khafhid Burhanudin (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2020)
Talking about the figure of Basuki Tjahaja Purnama alias Ahok is inseparable with a firm, hard, and authoritative nature. Public attention to the figure of Ahok seems not finished. Now he is trusted by the Ministry of State-Owned Enterprises (BUMN) to lead Pertamina as the chief commissioner. The news invited a variety of comments and responses from the public both in and against the policy. Appraisal system is an interpersonal system in functional linguistics which focuses on the negotiation of social relations about one's evaluation of something and someone. There are several dimensions of study in this appraisal system, which consists of attitude, graduation, and engagement. In this study, the writer will focus on the attitude study that appears in the compass's daily Instagram comments column. The method used in this study is a qualitative method. The theory used in this study refers to Martin's theory which is supported by Rose and White. Data collection techniques in this study emphasize the process of documentation. The results of the analysis of public comments indicate, public response to the existence of Basuki Tjahaja Purnama in the government is relatively balanced. This can be seen from the amount of polarity between positive and negative having the same amount, but has different patterns in the type of attitude that arises in the comments column.Kata kunci: Appraisal, Affect, Judgement, Appreciation, Polaritas, Ahok, Pertamina